Explicit and Latent Authority in Hierarchical Organizations - René van den Brink; Robert P. Gilles (Tinbergen Institute, 2003)
In this paper we consider the problem of the control of access to a firm's productive asset, embedding the relevant decisionmakers into a general structure of formal authority relations. Within such an authority structure, each decision maker acts as a principal to some decision makers, while she acts as an agent in relation to certain other decision makers. We study under which conditions decision makers decide to exercise their own authority and to accept their superiors' authority.We distinguish two types of behavior within such an authority situation. First, we investigate a non-cooperative equilibrium concept describing the explicit, myopic exercise of authority. We find that if monitoring costs are sufficiently small, such explicit authority is exercised fully.Second, we consider the possibility of subordinates to submit themselves to authority even though such authority is not enforced explicitly. Again for sufficiently small monitoring costs such latent authority can be supported as an equilibrium.
Keywords: C71; C79; D23; L23; 330; Cooperative games; Hierarchies; Social situations; Authority; Autorität; Hierarchie; Unternehmensorganisation; Kooperatives Spiel